2022
DOI: 10.14202/vetworld.2022.2072-2083
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the association between electrocardiogram parameters and left cardiac remodeling in dogs with myxomatous mitral valve disease

Abstract: Background and Aim: Electrocardiography (ECG) is an adjunct for cardiac enlargement diagnosis. However, its efficacy in assessing left cardiac remodeling (left atrial and left ventricular enlargement) in dogs with myxomatous mitral valve disease (MMVD) remains unclear. This study aimed to evaluate the association between ECG parameters and left cardiac remodeling and to investigate whether the rate of change in ECG waveforms in the same individual reflected left cardiac remodeling in dogs with MMVD. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…No significant difference was observed between the control group and B1 group. Previous studies of Isaka et al and Ogawa et al also reported no significant difference in LVIDDn between a control group and B1 group in various breeds of dogs [8,17]. Since LVIDDn is a normalized value based on body weight, it can be applied to various breeds, and it is presumed that the significant difference observed between stage B1 and B2 is a consequence of the cardiac enlargement caused by mitral regurgitation.…”
Section: Discussionmentioning
confidence: 94%
“…No significant difference was observed between the control group and B1 group. Previous studies of Isaka et al and Ogawa et al also reported no significant difference in LVIDDn between a control group and B1 group in various breeds of dogs [8,17]. Since LVIDDn is a normalized value based on body weight, it can be applied to various breeds, and it is presumed that the significant difference observed between stage B1 and B2 is a consequence of the cardiac enlargement caused by mitral regurgitation.…”
Section: Discussionmentioning
confidence: 94%